The German Auditory and Image (GAudI) vocabulary test: A new German receptive vocabulary test and its relationships to other tests measuring linguistic experience - Sandra Bethke; Antje S. Meyer; Florian Hintz (PLoS ONE, 2025)
Humans acquire word knowledge through producing and comprehending spoken and written language. Word learning continues into adulthood and knowledge accumulates across the lifespan. Therefore, receptive vocabulary size is often conceived of as a proxy for linguistic experience and plays a central role in assessing individuals’ language proficiency. There is currently no valid open access test available for assessing receptive vocabulary size in German-speaking adults. We addressed this gap and developed the German Auditory and Image Vocabulary Test (GAudI). In the GAudI, participants are presented with spoken test words and have to indicate their meanings by selecting the corresponding picture from a set of four alternatives. Here we describe the development of the test and provide evidence for its validity. Specifically, we report a study in which 168 German-speaking participants completed the GAudI and five other tests tapping into linguistic experience: one test measuring print exposure, two tests measuring productive vocabulary, one test assessing knowledge of book language grammar, and a test of receptive vocabulary that was normed in adolescents. The psychometric properties of the GAudI and its relationships to the other tests demonstrate that it is a suitable tool for measuring receptive vocabulary size. We offer an open-access digital test environment that can be used for research purposes, accessible via https://ems13.mpi.nl/bq4_customizable_de/researchers_welcome.php.